Acquired pulmonary stenosis due to compression by a bronchiogenic cyst. Issue 3 (May 1973) - Harris, M.; Woo-Ming, M. O.; Miller, C. G.
Abstract : A case of pulmonary stenosis due to extrinsic compression of the pulmonary artery and right ventricular infundibulum is reported. It is believed that this is the first such case recorded in the English literature where the cause of the compression was a bronchiogenic cyst.